University entrepreneurship center identity factors prioritization using TOPSIS method - Minouei, Amin; Zaidi abd Rozan, Mohd (International Journal of Engineering and Technology, 2018)
University Entrepreneurship Center Identity (UECI) is a set of meanings by which a UECI allows itself to be known, and through which it allows people to describe, remember and relate to it. There are many factors stated in many studies related to UECI, but their importance level is not mentioned. In this study, the UECI factors are ranked by using TOPSIS method. A quantitative study was conducted to obtain expertsâ€™ views on UECI factors. The UECI factors were prioritized and ranked by using the â€œTechnique for order of Preference by Similarity to Ideal Solutionâ€ (TOPSIS) from Multi-Criteria Decision Making (MCDM) method. The result of performing TOPSIS is as a novelty which assists UECI presentation. The high priority factors were introduced as â€œInnovativenessâ€, â€œIndustry Interactionsâ€, â€œProducing Highly Qualiï¬ed Graduatesâ€, â€œProactivenessâ€, â€œAttract Entrepreneurial Facultyâ€, â€œTeamworkâ€, â€œConsultingâ€, and â€œRisk Takingâ€. This study proposes the importance level of UECI factors. At the end, it is recommended to evaluate the effect of UECI perception in different studies which contain university entrepreneurship center identity perception.Â Â